Gagging Problem Assessment: a re‐evaluation. (12th February 2015) - van Linden van den Heuvell, G. F. E. C.; de Boer, B.; ter Pelkwijk, B. J.; Bildt, M. M.; Stegenga, B.
Summary The Gagging Problem Assessment (GPA) is an instrument to evaluate dental gagging. Although the GPA seemed to be reliable and valid in a pilot study, a replication study with more subjects was needed. Based on the pilot study, the number of items was reduced, resulting in the revised version of the GPA (GPA‐R). The aims of this study were to replicate the reliability of the GPA‐R and to investigate the correlation between dental gagging and general anxiety. Dental gagging patients (n = 59) were compared with a control group (n = 17) at t0 and 3 weeks later. The 'gagging group' also filled in the SCL‐90 anxiety scale. Gagging‐specific homogenous domains and internal consistency were determined. Stability and distinguishing capacity of the GPA‐R were assessed. SCL‐90‐Anxiety scores were compared with standard values in a non‐clinical population. The GPA‐R patient part was able to reliably discriminate between the absence or the presence of dental gagging. However, the reliability of the GPA‐R‐dentist part was insufficient. The GPA‐R seems to be sensitive to subtle differences in acts of the dentists. To overcome these problems, more detailed and explicit instructions on how to use the GPA‐R should be formulated and more specific gagging stimuli should be included. The 'gagging group' reported 'fear of choking' significantly more often than the control group (P = 0·008). This finding might be important for the treatment of dental gagging. Considering the outcome of our study, development of a new diagnostic gagging tool needs another approach that focuses on gagging severity.